Polyp Detection in Colonoscopy Video using Elliptical Shape Feature - Sae Hwang; JungHwan Oh; Tavanapong, W.; Wong, J.; de Groen, P.C. (2007 IEEE International Conference on Image Processing, 2007)
Early detection of polyps and cancers is one of the most important goals of colonoscopy. Computer-based analysis of video files using texture features, as has been proposed for polyps of the stomach and colon, has two major limitations: this method uses a fixed size analysis window and relies heavily on a training set of images for accuracy. To overcome these limitations, we propose a new technique focusing on shape instead of texture in this paper. The proposed polyp region detection method is based on the elliptical shape that is common for nearly all small colon polyps.